PENDAPATAN DAN STRATEGI PEMASARAN PETANI MELON DI KABUPATEN SELUMA - Evi Andriani; Ana Nurmelia; Wahyudi Wahyudi; Mujiono Mujiono (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2020)
This study aims to determine the income and marketing strategies of melon farmers in Seluma Regency. The study was conducted in July 2019. The population in this study amounted to 20 melon farmers. The type of data used in this study are primary data and secondary data. Data analysis methods used in this study are quantitative analysis and qualitative analysis. Quantitative analysis is used to calculate the level of income of melon cultivation with the calculation of farm income analysis. Meanwhile, qualitative analysis is used to determine the development strategy of melon cultivation using SWOT analysis. From this research, the average income of melon farmers in Seluma District was Rp 9,835,112,500 with an income of Rp 13,527,800,000 and expenditure costs of Rp 3,692,687,500. The strategy used in improving the marketing of melons is to sell melons with various processed variants of melons, marketing melons can be done with a partnership system, creating special transportation facilities in the process of melon distribution and increasing sales by adding product innovation Keywords : Melon, Revenue, Marketing strategy